The Effect of Expertise Time Constraints, Interactivity and Promotion on Impulse Purchases Live Streaming TikTok - Harahap, Tetty Rahmiati; Wahyuni, Erni (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
E-commerce is currently developing rapidly throughout the world. This development began when the Covid-19 outbreak occurred and was felt by people throughout the world and there were increasingly more forms of online transactions compared to manual ones. This research aims to analyze the relationship between live streaming-based online sales and impulsive buying using indicators of interactivity, expertise and promotion time limit. This research is quantitative descriptive. The population in this study were students using TikTok in Labuhanbatu Regency. The sampling technique used was non-probability sampling. A web-based online questionnaire was created using the application from google form. Respondents were invited via email, WhatsApp, with a message containing a link connected to a website containing the questions in the questionnaire, then filled in. The targeted sample of 100 participants from this research is expected to meet the requirements to participate in this research. The data obtained from the research was processed using data analysis techniques, namely multiple linear regression analysis using SmartPLS. The results of this research conclude that interactivity has a positive and significant effect on impulse buying. This means that the higher the interaction that streamers build in making online sales on TikTok Live Streaming the higher the impulse purchases made by consumers. Second, this research also found that expertise has a positive and significant effect on impulse buying. the expertise a social media influencer possesses can greatly determine a customer's level of engagement, and therefore, their intent to purchase as well. In this way, the higher the expertise the streamer has in making sales on live streaming The higher the rate of impulsive betting that occurs during live streaming. Lastly, promotion time limits have a positive and significant effect on impulse buying. This means that the more promotional exposure felt by consumers, the higher the impulse purchases made during live streaming. Time limit marketing is a strategy for marketing products by providing limited time to create pressure for buyers so that they can speed up the process of making purchasing decisions.